2014
DOI: 10.1161/circoutcomes.113.000706
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Completeness and Accuracy of Case Ascertainment in the Michigan Stroke Registry

Abstract: The MSR collects information on the quality of acute stroke care as part of the Centers for Disease Control and Prevention Paul Coverdell National Acute Stroke Registry.3 Hospitals were selected through a stratified complex sampling scheme (based on geography, urban versus rural setting, and minority status [black versus white]) to obtain a representative statewide sample of hospitals providing acute stroke care. Human subjects' approval was obtained from the Michigan Department of Community Health institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In a 1992 study, a sensitivity of 96% and a PPV of 100% were reported for the Northern Sweden MONICA Registry [14], whereas a recent study found that the Danish Stroke Registry had a sensitivity of 97% and a PPV of 90% [15]. The sensitivity and PPV of the Michigan Stroke Registry were reported to be 68.8 and 87.7%, respectively, in a 2014 study [16]. The results from the present study indicate a lower sensitivity for the Stroke Register than in these two European studies and a higher sensitivity than that found in the US study.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1992 study, a sensitivity of 96% and a PPV of 100% were reported for the Northern Sweden MONICA Registry [14], whereas a recent study found that the Danish Stroke Registry had a sensitivity of 97% and a PPV of 90% [15]. The sensitivity and PPV of the Michigan Stroke Registry were reported to be 68.8 and 87.7%, respectively, in a 2014 study [16]. The results from the present study indicate a lower sensitivity for the Stroke Register than in these two European studies and a higher sensitivity than that found in the US study.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Over a 3 year period from 2009 to 2011, a total of 22 382 cases from 36 hospitals were included in the registry. Human subjects' approval was obtained from the Michigan Department of Community Health IRB.…”
Section: Registry Design and Data Collectionmentioning
confidence: 99%
“…The number of patient registries will continue to rise in the near future [21]. Their importance was shown in many areas including general practice [22], neurology [23,24], orthopedics [25,26], and oncology [27,28].…”
Section: Future Prospects Of Registriesmentioning
confidence: 99%